MANAJEMEN KELAS MIN 1 TELADAN PALEMBANG - Tutut Handayani; Mardiah Astuti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2018)
Class management is an aspect of education that is often the main concern by prospective educators, new educators, and even experienced educators. Because prospective educators, new educators, and educators who are experienced wish that students can learn optimally. In the sense that educators are able to convey lesson material and can be accepted by students well. How to direct and guide students to learn well, the answer to this question is that educators must be able to create a classroom atmosphere that is able to support learning activities, one of which is by having good classroom management so that learning takes place effectively. This research was conducted at MIN 1 Teladan Palembang with the formulation of the problem of how class management at MIN 1 is the Exemplary Palembang